Definition and Role of Sustainable Materials in Reaching Global Sustainable Development Goals (SDGs) Completed with Bibliometric Analysis - Risti Ragadhita; Asep Bayu Dani Nandiyanto; Obie Farobie; Teguh Kurniawan; M. Roil Bilad (Bumi Publikasi Nusantara, 2026)
Sustainable materials are essential in achieving the Sustainable Development Goals (SDGs), particularly in clean energy, water purification, waste reduction, and green infrastructure. This study investigates the role of material innovation in supporting the SDGs using a Systematic Literature Review (SLR) and bibliometric analysis (from Scopus database (2015–2025) using keywords “Sustainable Material,” “Green Material,” and “SDGs”). The findings showed a growing research trend, especially after the COVID-19 pandemic, with significant contributions from chemistry, engineering, and environmental sciences. Materials like nanomaterials, biomaterials, biodegradable polymers, and waste-derived products contribute to SDG 6, 7, 9, 12, and 13. Innovations such as green nanotechnology, bio-based materials, and circular material design show strong potential to address global sustainability challenges. These materials not only support emission reduction and waste valorization but also encourage green job creation and sustainable production. This study highlights interdisciplinary pathways to align material science with sustainable development.